Modulation of Cellular Function by the Urokinase Receptor Signalling: A Mechanistic View - Alfano, Daniela; Franco, Paola; Stoppelli, Maria Patrizia (Frontiers in Cell and Developmental Biology, 2022)
Urokinase-type plasminogen activator receptor (uPAR or CD87) is a glycosyl-phosphatidyl-inositol anchored (GPI) membrane protein. The uPAR primary ligand is the serine protease urokinase (uPA), converting plasminogen into plasmin, a broad spectrum protease, active on most extracellular matrix components. Besides uPA, the uPAR binds specifically also to the matrix protein vitronectin and, therefore, is regarded also as an adhesion receptor. Complex formation of the uPAR with diverse transmembrane proteins, including integrins, formyl peptide receptors, G protein-coupled receptors and epidermal growth factor receptor results in intracellular signalling. Thus, the uPAR is a multifunctional receptor coordinating surface-associated pericellular proteolysis and signal transduction, thereby affecting physiological and pathological mechanisms. The uPAR-initiated signalling leads to remarkable cellular effects, that include increased cell migration, adhesion, survival, proliferation and invasion. Although this is beyond the scope of this review, the uPA/uPAR system is of great interest to cancer research, as it is associated to aggressive cancers and poor patient survival. Increasing evidence links the uPA/uPAR axis to epithelial to mesenchymal transition, a highly dynamic process, by which epithelial cells can convert into a mesenchymal phenotype. Furthermore, many reports indicate that the uPAR is involved in the maintenance of the stem-like phenotype and in the differentiation process of different cell types. Moreover, the levels of anchor-less, soluble form of uPAR, respond to a variety of inflammatory stimuli, including tumorigenesis and viral infections. Finally, the role of uPAR in virus infection has received increasing attention, in view of the Covid-19 pandemics and new information is becoming available. In this review, we provide a mechanistic perspective, via the detailed examination of consolidated and recent studies on the cellular responses to the multiple uPAR activities